Studi Kasus: Dampak Panjang Kabel Penghantar terhadap Drop Tegangan dalam Distribusi Daya dari Generator ke Motor Induksi 3 Fasa di Unit Screw Press PTP Nusantara II Sawit Hulu - Tambunan, Bayu Hillam Saputra; Karti, Karti (CV. IRA PUBLISHING, 2023)
Voltage drop is the amount of voltage lost in a conductor. The voltage drop on electric power lines is generally directly proportional to the length of the line and the load and inversely proportional to the cross-sectional area of the conductor. The magnitude of the voltage drop is expressed either in percent or in Volts. The analysis determines the voltage drop in the power distribution from the generator to the three-phase induction motor at PT. Perkebunan Nusantara II Sawit Hulu uses 30 meters of copper conductor cable with a cross-sectional area of 400 mm2. This type of copper wire material has an absolute sending voltage value of 389 volts and a total receiving voltage value of 385. So there is a voltage drop based on the length of the conducting cable of 4 Volts, and if it is a percentage, the voltage drop value is 1.03%.